2002
DOI: 10.1038/sj.ejcn.1601645
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and lifestyle interventions in the management of the metabolic syndrome: present status and future perspective

Abstract: Objective: To review the mechanisms underlying the metabolic syndrome, or syndrome X, in humans, and to delineate dietary and environmental strategies for its prevention. Design: Review of selected papers of the literature. Results: Hyperinsulinemia and insulin resistance play a key role in the development of the metabolic syndrome. Strategies aimed at reducing insulin resistance may be effective in improving the metabolic syndrome. They include low saturated fat intake, consumption of low-glycemic-index foods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Genetic, metabolic, and various environmental and social factors have been considered as risk factor for MetS. Hence, the identification of socioeconomic characteristics associated with MetS is essential for successful primary prevention [7, 8]. Moreover, social factors such as education level, occupation, household income, and marital status may influence MetS [9].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic, metabolic, and various environmental and social factors have been considered as risk factor for MetS. Hence, the identification of socioeconomic characteristics associated with MetS is essential for successful primary prevention [7, 8]. Moreover, social factors such as education level, occupation, household income, and marital status may influence MetS [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although, the exact mechanism involved in this relationship is not clear, the socio-economic status may influence MetS and its components by affecting environmental and social factors [22,23]. Therefore, as an initial preventive approach to understand and manage the occurrence of MetS, it appears warranted to study the social and economic variables that could lead towards its high prevalence [24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that lifestyle choices, accumulated across the life course, greatly influence the risk of developing non-communicable diseases, such as hypertension, obesity, dyslipidaemia, and diabetes mellitus [15,16]. Studies assessing the aetiology of these diseases have increasingly focused on genetic and environmental factors [17][18][19].…”
Section: Introductionmentioning
confidence: 99%